The Historical Relevance of the Indonesian National Movement in the Merdeka Curriculum - Jaza Ana Albirru (JURNAL HISTORICA, 2023)
The research used is a qualitative research method that is descriptive by explaining systematically. The method used is library research, by searching for data from various data sources such as journals, articles, and existing books. The purpose of writing this journal is to find out the great relevance of the history of the Indonesian national movement in the independent curriculum, and to provide an understanding of the history of the Indonesian national movement to the public, students, and other readers. The Indonesian National Movement was a form of protest against the colonists' oppression of the Indonesian people carried out for many years, who were born in 1908-1945. The independent curriculum in the application of learning can be done only not in the classroom but also outside the classroom. "Merdeka Belajar" curriculum with the aim to provide opportunities for students to develop their talents. Keywords: history of movement, independent curriculum, history